Etude des préférences des consommateurs vis -à- vis les produits laitiers et les fromages locaux de la ville d’Oran - Assiane, Rania Fatima Zahra (My University, 2023)
In order to understand the preferences and consumption patterns of dairy products and local cheeses by consumers, a survey was conducted over two weeks among 20 customers of large stores manufacturing-sellers of local dairy products and cheeses in the city of Oran. The results showed that the consumption of milk and dairy products was more related to sociocultural belonging than to income. Cheese is the most consumed dairy product (55%). The study confirmed the growing interest of certain consumers in local products. The reasons given are diverse and range from attachment to local produce, organoleptic qualities and the source of milk. In the end, he showed his satisfaction
Keywords: Local dairy products; Traditional cheese; Preferences; consumption; satisfaction